Chondroprotective potential of Phyllanthus amarus Schum. & Thonn. in experimentally induced cartilage degradation in the explants culture model - Pradit,W. (Springer New York, 2015)
© 2014, The Society for In Vitro Biology. Phyllanthus amarus Schum. & Thonn. (P. amarus) has been reported to exhibit anti-inflammation and antiarthritis properties leading to our interest to examine its beneficial effect in osteoarthritis. Thus, this study aimed to explore the chondroprotective potential of P. amarus extract (PAE) and its major compounds, phyllanthin and hypophyllanthin, in a cartilage explant model. Various concentrations of P. amarus extract, phyllanthin and hypophyllanthin, were treated on porcine articular cartilage explants induced with 25 ng/ml of interleukin-1 beta (IL-1β). After 4 days of incubation, the culture medium was measured for the release of sulfate glycosaminoglycans (s-GAGs) and matrix metalloproteinase-2 (MMP-2) activity by DMMB binding assay and zymography, respectively. The explant tissues were analyzed for the remaining of uronic acid content by colorimetric assay and stained with safranin-O for investigation of proteoglycan content. Cell viability of this model was evaluated by lactate dehydrogenase (LDH) assay. Chondroprotective potential of PAE and the major components against IL-1β-induced cartilage explant degradation were revealed by the decreased s-GAGs level and MMP-2 activity in culture medium consistent with an increase in uronic acid and proteoglycan contents in the explants when compared to the IL-1β treatment. These results agreed with those of diacerein and sesamin which used as positive controls. In addition, better chondroprotective activities of P. amarus crude extracts than those of the purified components were disclosed in this study. Hence, this is a pioneering study presenting the chondroprotective potential of PAE which may augment its application for therapeutic use as an antiarthritic agent.